Nova does not mean "it doesn’t go". - Shore, Anthony (Language at Work - Bridging Theory and Practice, 2010)
The marketing myth persists that the Chevy Nova did not sell well in Latin America because "no va" means "doesn’t go" en Español. But the Nova legend is a lie – a tenacious one at that.